Transverse shear deformability in the dynamics of thin-walled composite beams: consistency of different approaches - Piovan, Marcelo Tulio (2005)
The aim of this work is to describe an analysis of the transverse shear deformation in the dynamics of thin-walled composite beams. Some thin-walled-composite-beam models, which are derived by means of different approaches (principle of virtual works and principle of Hellinger-Reissner among others), show substantial discrepancies due to the employment of different consitutive equations based on the aforementioned approaches. In the following paragraphs a comparison of different schemes and hypotheses related to constitutive equations for thin-walled composite beams is performed.